2020
DOI: 10.1097/md.0000000000022639
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in the treatment of human immunodeficiency virus-negative tuberculous meningitis

Abstract: Introduction: Tuberculous meningitis (TBM) is the most fatal type of tuberculosis in which corticosteroids are added with antitubercular therapy to prevent permanent brain damage. However, this treatment may produce paradoxical reactions. In such cases, thalidomide use might reduce central nervous system inflammation and improve the outcome. We present the case of a human immunodeficiency virus-negative patient with TBM who developed paradoxical reactions manifesting as multiple intracranial tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The association of elevated TNF‐α in lumbar and ventricular CSF and infarction has been reported in earlier studies 35,36 . TNF‐α blocker therefore has been tried in some patients with persistent tuberculoma 37 ,. CSF concentration of 100 unit/ml of TNF‐α can damage human endothelial cells in vitro 38 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The association of elevated TNF‐α in lumbar and ventricular CSF and infarction has been reported in earlier studies 35,36 . TNF‐α blocker therefore has been tried in some patients with persistent tuberculoma 37 ,. CSF concentration of 100 unit/ml of TNF‐α can damage human endothelial cells in vitro 38 .…”
Section: Discussionmentioning
confidence: 72%
“…35,36 TNF-α blocker therefore has been tried in some patients with persistent tuberculoma. 37 , CSF concentration of 100 unit/ml of TNF-α can damage human endothelial cells in vitro. 38 Animal study has shown the role of TNF-α in formation and maintenance of granuloma.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, a full-text review was performed for 26 articles, and finally, 14 articles satisfied all the inclusion criteria for our review (Supplemental Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] One prospective study by van Toorn et al 16 was excluded, as all the patients included in this study were also part of the retrospective study published by the same author in 2020. 17 Out of these 14 studies, one was a double-blind placebo-controlled RCT, one was a phase II nonrandomized controlled trial comparing various doses of thalidomide between 6 mg/kg/day, 12 mg/kg/day, and 24 mg/kg/ day, one was a retrospective cohort study, five were case series, and six were single case reports.…”
Section: Resultsmentioning
confidence: 99%
“…Out of all the patients who received thalidomide, 17 were HIV-positive, 14 (82%) had a favorable response, and all of them had some or other evidence of IRIS and had recently started combination ART for HIV status. [7][8][9][10][11][12][13][14][15][16][17][18][19] All of them were severely immunocompromised with a median CD4 count of 71 cells/mm 3 . Overall, the median time from the start of ATT to the development of TB-IRIS was 1.8 months (IQR: 0.8-5.9 months), whereas in HIV-positive cases it occurred after a median of 0.9 months (IQR: 0.3-1.8 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation